Impact of Human Rhinovirus Types and Viral Load on the Severity of Illness in Hospitalized Children With Lower Respiratory Tract Infections. Issue 11 (November 2015) - Xiao, Qiuyan; Zheng, Shouyan; Zhou, Lili; Ren, Luo; Xie, Xiaohong; Deng, Yu; Tian, Daiyin; Zhao, Yao; Fu, Zhou; Li, Tingyu; Huang, Ailong; Liu, Enmei
Abstract : Background: Human rhinovirus (HRV) is not only responsible for at least one-half of all common colds but also associated with bronchitis, bronchiolitis, pneumonia and acute asthma exacerbation. However, the impact of different HRV types and viral load on disease severity has not been thoroughly elucidated. Methods: From January 2012 to September 2014, 1742 nasopharyngeal aspirate specimens from hospitalized children with lower respiratory tract infections were analyzed by quantitative HRV-specific real-time polymerase chain reaction. Results: Among these 1742 children, HRV (407/1742, 23%) was the second most common viral agent after respiratory syncytial virus. HRV-A, HRV-B, HRV-C and HRV untyped were detected in 229 (56%), 27 (7%), 100 (25%) and 51 (13%) specimens, respectively. Children except who experienced wheezing were more common in the HRV-C detection group than in the HRV-A detection group; there were no other significant differences between the 2 groups, including the percent of children diagnosed with severe diseases. Logistic regression models demonstrated that there was no difference in disease severity among HRV types. In HRV-A detection group, in children younger than 2 years, the viral load was higher in the severe group than in the nonsevere group; but in the HRV-C detection group, there was no difference. Conclusions: HRV was frequently present in hospitalized children with lower respiratory tract infections in Chongqing, China. The disease severity for HRV-C and HRV-A was similar. A high load of HRV-A in the lower respiratory tract might be connected with disease severity in children younger than 2 years.